Testing specialization hypothesis on a stress gradient. (7th June 2016) - Fazlioglu, Fatih; Wan, Justin S. H.; Bonser, Stephen P.
Abstract: Specialization can allow plants to perform well in their home environments at the expense of poor performance in other habitats. A great difference in performance across habitats is observed as high phenotypic plasticity in performance traits and a by‐product of selection. However, phenotypic plasticity (particularly adaptive plasticity) can be an active response to the selection by allowing the maintenance of performance. Therefore, specialization and adaptive plasticity delineate two opposing strategies. The specialization hypothesis presents a non‐adaptive interpretation of plasticity and predicts that phenotypic plasticity of performance traits is greater in specialization to good habitats, whereas bad habitat specialists express low plasticity in performance traits. We tested the specialization hypothesis using plants adapted to extremely stressful mine‐site habitats (sites with highly acidic soil and heavy metal contamination). Seeds of five herbaceous species were collected from high stress (mine site) and low stress habitats. We established a glasshouse experiment where seedlings from high and low stress habitats were grown under near neutral pH and acid soil treatments. We compared performance trait plasticity (e.g. biomass) from high stress and low stress populations and found that there was no significant difference in performance traits between high and low stress populations across treatments. The overall result did not support the specialization hypothesis. Moreover, our results suggest that the species invaded the mine sites are either extreme generalists or the surrounding populations retain some stress tolerant genotypes that are capable of invading the mine sites.